Analysis of climate change primary concepts in science, health and environment textbooks of primary school in Afghanistan - Mortaza Kazemi (World Journal of Advanced Research and Reviews, 2022)
Globalized and interconnected world subject of climate change conditions become crucially vital for individuals and communities in local and international level due to protecting the earth and its livelihoods of species, so students as change agents need to be educated to be conscious, sensible about climate change impacts, adaptations, and mitigations which enabling them to reduce the vulnerability of themselves and their society to risk and contribute to sustainable development. Therefore, the purpose of this study was to analyze the content and illustrations of primary school Science, Health and Environment textbooks based on climate change causes, impacts, and solutions as indicators. The content analysis has been performed as research method in two sections such as 1) conceptual analysis, and 2) pictorial analysis which the results have been transferred to tables and interpreted. According to the findings, most of the concepts and pictures were assigned to climate change impacts that following with climate change causes, while climate change solutions received less attention in both texts and illustrations. The majority of the concepts have been discussed from biology, physics, and chemistry perspectives rather than climate change point of view which in turn underpinned the explicitly of the concepts. However, the pictorial representations were more explicit and were drawn a clear linkage to climate change trends. Nonetheless, local concerns need to be taken in consideration to reduce the irreversible impacts of climate change on economic, political, social and cultural spheres.